Diasporic daughters and digital media: 'willing to go anywhere for a while'. Issue 3 (3rd May 2016) - Kim, Youna
ABSTRACT: This study explores the paradoxes of digital media as place-making practices in the lived and mediated experiences of relatively silent or invisible groups of migrants – educated and highly mobile generations of Korean, Japanese and Chinese women in London. One of the striking features in the transformational nature of international migration today is the salience of provisionality and the nomadic symptom ('willing to go anywhere for a while'), as evident among the East Asian women in this study. Underlying the processes of circulatory migration flows, modes of social organization and transnational experiences are the accelerated globalization of digital media, Internet and its time–space compressing capacity. As this study will argue, today's circulatory migration and provisional diaspora is significantly enabled, and driven in part, by the strategic and mundane use of mediated cultural spaces, through which movements are not necessarily limited but are likely to increase in their impact, and further sustained in various transnational contexts, albeit with unintended consequences. The electronic mediation of Internet plays a significant role not just in facilitating the ongoing physical mobility and possibly maintaining its long-term durability, but also crucially in constituting and changing the way in which diasporic lives and subject positions are experienced and felt in otherwise a sense of placeless-ness. New spaces, connections and various capacities of mobility are now changing not only the scale and patterns of migration but also the nature of migrant experience and thinking, and therefore the complex conditions of identity formation.